The influence of self-esteem on effective leadership style - Călin, Mariana Floricica; Sandu, Mihaela Luminița (Technium Social Sciences Journal, 2021)
An organization is the combination and use of resources - human, financial and material - to achieve goals. All organizations include in one form or another a set of their own goals, the distribution of power and authority, expectations about functions or duties, communication channels, and certain methods of ensuring that goals are achieved. The universal nature of organizations has made them the subject of both admiration and negative jokes or stories. On the one hand, some organizations are said to be "anointed," while in others people complain that they are treated like numbers, not individuals, or that they get lost in the big bureaucracy.